Developing Plugin e-DDC as an Additional Application for Senayan Library Management System with PHP Language Programming and MySQL Database - Rotmianto, Mohamad; Wahyudi, Eko (Record and Library Journal, 2016)
Senayan Library Management System, usually called as SLiMS dan e-DDC (electronic Dewey Decimal Classification), is an application for library that now is used widely because it is easy to use, guaranteed of updating from the provider, and free. SLiMs and e-DDC is actually two separated application, but in the practice, it is possible and recommended to be used together. SLiMS is used as a tool of library automation, meanwhile e-DDC functions to help finding collection classification number. Some users of SLiMS and e-DDC have suggested to develop SLiMS that is integral with e-DDC, so the use of both application can be practical which can make the librarian easier to manage the library. Based on the suggestion, the writer and e-DDC team finally created and designed additional application which is called plugin in SLiMS automation system that contained e-DDC. The plugin was created using PHP MySQL and MySQL database. The purpose of this paper is to enrich the reference of library application development, especially that is based on Free Open Source Software (FOSS). The method used is Research and Development method. The result was the Plugin e-DDC for SLiMS was finished and released on May 2, 2015 to celebrate National Education Day.